2020
DOI: 10.21203/rs.3.rs-34730/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the COVID-19 virus outbreak on movement and play behaviours of Canadian children and youth: A national survey

Abstract: Background: Healthy child and youth development is fostered through sufficient physical activity (PA; including time outdoors), limiting sedentary behaviours (SB), and adequate sleep; collectively known as movement behaviours. Though the COVID-19 virus outbreak has changed the daily lives of children and youth, it is unknown to what extent related restrictions may compromise the ability to play and meet movement behaviour recommendations. This study examined the immediate impacts of COVID-19 restrictions on mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

47
294
12
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(363 citation statements)
references
References 27 publications
47
294
12
10
Order By: Relevance
“…Our finding of a decrease in all types of PA (i.e., MPA, VPA and walking) after the COVID-19 outbreak are consistent with a recent national survey in Canada, which reported a significant decline in all physical activities in children and adolescents [ 15 ]. The cross-sectional analysis also revealed the low volume of PA that participants engaged in during the COVID-19 pandemic, with an average of 3 min/day spent in MPA and 17 min/day walking.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our finding of a decrease in all types of PA (i.e., MPA, VPA and walking) after the COVID-19 outbreak are consistent with a recent national survey in Canada, which reported a significant decline in all physical activities in children and adolescents [ 15 ]. The cross-sectional analysis also revealed the low volume of PA that participants engaged in during the COVID-19 pandemic, with an average of 3 min/day spent in MPA and 17 min/day walking.…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with a national survey, which reported that daily sitting time increased from 5 to 8 h (28.6%) per day during home confinement [ 18 ]. Similarly, children and adolescents in both Shanghai and Canada engaged in more than 5 h of screen time per day [ 14 , 15 ]. This may be partially explained by young adults engaging in social distancing by staying home, and online teaching, which subsequently resulted in prolonged screen time, such as elevated time spent watching TV, playing computer games, and online teaching [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The government declared a nationwide lockdown from March 26 to May 30, with a 7 th extension being recently announced [ 17 , 18 ]. Previous studies investigated the impact of COVID-19 on physical activity in different age clusters and in different regions [ 19 , 20 , 21 ]. Reports have indicated that the COVID-19 pandemic-related public health restrictions appear to have led to reductions in physical activity [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The currently available data speak in favour of a strategy of future prevention concepts differentiated according to the age of the children and adolescents in order to minimise the risk of infection events, to limit them and to prevent the blanket closure of day-care centres and schools as a first measure [ 38 ], [ 39 ], [ 40 ]. Continuous attendance at a day-care centre [ 41 ] or school is not only essential for the sustainable educational success of the next generation, but also for healthy and successful development through social contacts, developmental tasks and challenges [ 42 ], [ 43 ], [ 44 ], [ 45 ]. In addition, it leads to a relief of the families and also to a release of the labour force of the persons having custody (compared to the continuous care of small children at home or the digital home-schooling of school children) [ 46 ], [ 47 ], [ 48 ], [ 49 ], [ 50 ], [ 51 ], [ 52 ].…”
Section: Introductionmentioning
confidence: 99%